Association between severe psychological distress and spousal alcohol drinking status among married couples in Japan: a cross-sectional study using nationally representative survey data - Tasuku Okui (BMC Public Health, 2026)
Abstract Background Spousal alcohol drinking status is known to affect individuals’ psychological distress in some countries; however, the effect modification of the association between spousal alcohol drinking status and individuals’ psychological distress by their own alcohol drinking status has been scarcely investigated. Therefore, we investigated this association using nationally representative survey data. Methods Data of married couples obtained from the Comprehensive Survey of Living Conditions were used in this cross-sectional study. Alcohol consumption was categorized into non-/seldom, moderate, and heavy drinkers, and drinking history was categorized into never, former, and current drinkers. A generalized estimation equation Poisson model was used to investigate the association between severe psychological distress and spousal alcohol drinking. In addition to a crude analysis, an adjusted analysis taking into account other characteristics was conducted. Moreover, a subgroup analysis considering respondents’ own alcohol drinking status was conducted. Results Upon analyzing 65,192 couples, no statistically significant associations of the severe psychological distress of husbands with alcohol consumption and drinking history of their wives were observed. In contrast, non-/seldom drinking among husbands was significantly associated with a higher prevalence of severe psychological distress among wives, and the subgroup analysis found significant associations among wives who were non-/seldom and moderate drinkers. In addition, heavy alcohol drinking among husbands was significantly associated with a higher prevalence of severe psychological distress among wives, and the subgroup analysis found a significant association only among wives who were non-/seldom drinkers. Moreover, former drinking among husbands was significantly associated with a higher prevalence of severe psychological distress among wives who were never drinkers, and never drinking among husbands was significantly associated with a higher prevalence of severe psychological distress among wives who were current drinkers. Conclusions The alcohol drinking status of husbands was associated with the severe psychological distress of their wives, and the significance of the association depended upon alcohol drinking status of wives.